Effects of Lavender, Lemon and Eucalyptus Essential Oil on Th2 related Factors of DNCB-induced Atopy dermatitis in NC/Nga Mice Model - Kim, Hyeon-Ah; Yun, Mi-Young; Song, Hyang-Hee; Cheong, Kwang-Jo; Yoo, Hwa-Seung (Korean Pharmacopuncture Institute, 2010)
Purpose : To investigate the effects of the lavender, lemon and eucalyptus oil mixture on the atopy dermatitis skin lesions induced on NC/Nga Mice by dinitrochlorobenzene (DNCB). Material and Method : For this purpose, we fabricated the oil mixture blending three essential oils (lavender, lemon, eucalyptus : ELL) with one carrier oil (jojoba) and apply it on the atopic dermatitis skin lesions of NC/Nga Mice. Atopic dermatitis in NC/Nga Mice was induced by DNCB treatment on the dorsal skin of mice for 8 weeks. The mixture of ratio of each essential oil drop was 1 (eucalyptus) : 2 (lemon) : 2 (lavender) and this mixture was blended with jojoba oil 50ml (0.025%). The ELL-ointment was supplied for 8 weeks. We evaluated the effects of ELL on cell viability of mouse lung fibroblast, clinical skin features and severity, the level of serum Immunoglobulin (Ig) E & Ig G1, Interleukin (IL)-4, IL-13 and Interferon (IFN)-. Results : ELL showed safety on the cell viability of mouse lung fibroblast compared with control group. The cell viability was measured by SRB method. The effects of ELL on clinical skin features and severity in DNCB-induced dermatitis model of NC/Nga mice was significant compared with control group. EEL also showed significant effects on clinical symptom score compared with control group. Serum IgE & IgG1 level and development of atopy dermatitis skin lesions were evaluated. Serum IgE & IgG1 production was significantly down-regulated in EEL group compared with control group. ELL also down-regulated the levels of IL-4 and IL-13, and up-regulated the level of IFN- compared with control group significantly. Conclusion : ELL was effective on atopy dermatitis by modulating Th2 related factors.